Estimation of Geothermal Potential Area in Kabawetan Sub-District, Using 2D Magnetotelluric Inversion Method - Gumanty, Usman; Refrizon, Refrizon; Azzahra, Gusti Ayu Zahwa; Nurhayati, Ratna Dewi; Al Ansory, Andre Rahmat; Raihana, Hana; Farid*, Muchammad (Aceh International Journal of Science and Technology, 2025)
Kabawetan is located in the subduction zone of the magmatic arc in the Indonesian tectonic system. The geothermal energy potential in this region is closely tied to volcanic activity, which is prevalent along the Ring of Fire on the island of Sumatra. This study aims to identify the distribution of subsurface resistivity values related to geothermal potential in the Kabawetan Region. To achieve this, the magnetotelluric (MT) method is used, utilizing electrical and magnetic sensors. Data were collected using two horizontal electrical sensors (Ex, Ey) and three magnetic sensors, including two horizontal sensors (Hx, Hy) and one vertical sensor (Hz). Measurements using the magnetotelluric method can be used to determine the subsurface rock layers based on resistivity values. The results of data processing yield a 2D cross-section of the resistivity value, which characterizes the potential for geothermal energy. This study used four measurement points to analyze resistivity variations and determine geothermal potential. Field measurement data were processed using MAPROS software, and a 2D cross-section model was created using ZONDMT2D. The results showed that resistivity values of 20-60 m, thought to be impermeable overburden, were at depths of 0-1.5 km and 2.5-4 km, resistivity values of 0.54-1 m indicated permeable reservoirs at depths of 1.5-2.5 km, and resistivity values of 290-550 m indicated geothermal rocks at depths of 4-10 km. The findings of this research are expected to enhance the understanding of geothermal energy as a renewable resource, thereby supporting the Sustainable Development program.